التعايش السلمي بين المسلمين وغيرهم في بولاو بينانج : دراسة تحليلية تقويمية في ضوء مقصد حفظ الأمن - Wan Nor Fathihah Wan Ahmad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research discussed the Peaceful Coexistence and its importance in achieving state security Maqṣad al-Amn in the community of Penang. It is one of the states in Malaysia where people live in a society comprised of different backgrounds in terms of religion, culture and language, but is currently governed by non-Muslims. The method used in this study is the inductive method in order to understand peaceful coexistence in Penang in light of Maqṣad al-Amn. The current paper also used an analytical approach in order to respond to the issues in Penang. Additionally, the research analysed the history of Malaysia, Penang and its society from the Malays, Chinese, Indians, and the minorities of Baba Nyonya and Jawi Peranakan. The researcher explained the roles of human beings as a successor in this world, peaceful coexistence in accordance to Islamic jurisprudence, and gave suggestions in achieving the goal of Maqṣad al-Amn in the Penang community. It is hoped that the research benefits the Malaysian community in general and the Penang community in particular in promoting national unity through the application of the Maqṣad al-Amn.